Extracellular matrix protocols - Ram, Sharona Even (Humana, 2012)
The study of the extracellular matrix has significantly expanded over the past decade. Although thoroughly researched, the complexity and the dynamic nature of the matrix are still under extensive investigation, yielding a growing number of methods of analysis. In Extracellular Matrix Prools: Second Edition, expert researchers explore this developing field and provide a number of techniques which can be reproduced in most cell biology labs. This edition contains methods that represent cutting edge unique technologies which are well worth exposure to the broad field and may encourage collaboration with expert labs. Chapters include information on molecular biology techniques to study gene expression, biophysical and biochemical methods for the analysis of structure and composition, and cell biology methods for assessment of cell behavior, matrix assembly and tissue engineering applications. Composed in the highly successful Methods in Molecular Biology™ series format, each chapter contains a brief introduction, step-by-step methods, a list of necessary materials, and a Notes section which shares tips on troubleshooting and avoiding known pitfalls.